“The Renovating Fury”: Southey, Republicanism and Sensationalism - Haywood, Ian (Romanticism on the Net, 2003)
AbstractThis article takes a fresh look at Southey’s radical poetry of the 1790s in order to assess Southey’s mobilization of the tropes of political violence and atrocity. In the repressive antijacobin climate of the mid to late 1790s, radicalism was frequently associated with the sensational imagery of unbridled popular violence and regicide, but such propaganda misrepresented the ways in which radical authors like Southey used their texts precisely to explore and negotiate the problem of “justified” violence. The two texts I focus on are Wat Tyler and Joan of Arc, both of which imagine the bloody overthrow and destruction of a violent British state. But I show that beneath such a sensational vision (which may seem to explain why Wat Tyler was not published) is a more complex and coded engagement with the contemporaneous debate about politics, violence and democracy, including issues such as plebeian chivalry, heroic martyrdom, divine punishment, and state terror. I also argue that the furore surrounding the radical pirating of Wat Tyler in the postwar period overlooked the fact that the text offers the reader various political fantasies and discourses of violence ranging from regicide to patriarchal self-defence, sacrificial defiance and statesmanlike moral reflection. I hope to show, therefore, that a more nuanced historicist approach to Southey’s early poetry in fact yields a more polysemic hermeneutics than has been appreciated by critics from the Romantic period to the present.